"Es gibt nichts Gutes, außer man tut es" - Arbeit an der Verständlichkeit von Gesetzestexten in der Schweizerischen Bundeskanzlei - Nussbaumer, Markus (HERMES - Journal of Language and Communication in Business, 2002)
In recent years, some attempts have been made to establish guidelines for the drafting of statutory texts. None of these, however, have been very successful. Still, the need for such guidelines is felt. Over the last 25 years, the language sections of the Swiss Federal Chancellery (Sprachendienste der Schweizerischen Bundeskanzlei) have worked with optimising statutory texts. The article presents some of the principles, on which the work of the language sections is based, and underlines the importance of creating necessary institutional structures for optimising such texts. For optimisation can only be successful if language specialists are seriously involved in the whole drafting process.